2012
DOI: 10.5144/0256-4947.2012.462
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of attention deficit hyperactivity symptoms in female schoolchildren in Saudi Arabia

Abstract: BACKGROUND AND OBJECTIVESAttention deficit hyperactivity disorder (ADHD) is the most commonly seen developmental disorder, with significant impacts on the child’s social, psychological, and scholastic functioning. The aim of this study was to determine the prevalence and sociodemographic correlates of ADHD in female primary schoolchildren.DESIGN AND SETTINGA cross-sectional study conducted in Al-Khobar Town, Eastern Saudi Arabia.METHODSA random sample of six primary schools for girls was chosen, from which sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
6
20
1
Order By: Relevance
“…Our results are comparable to those of other studies conducted in Arab countries, which have shown that ADHD is more noticeable among children aged 6-9 years and the symptoms start to regress after 11 years (8,12,13,17).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our results are comparable to those of other studies conducted in Arab countries, which have shown that ADHD is more noticeable among children aged 6-9 years and the symptoms start to regress after 11 years (8,12,13,17).…”
Section: Discussionsupporting
confidence: 82%
“…These results are in line with the findings of studies conducted in Saudi Arabia, Kuwait and Qatar (8,12,13,17,18), and could be explained by the fact that children in large families receives less care, which results in behavioural problems being observed more often among these children.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations